2017
DOI: 10.1111/wrr.12537
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of Concern: The effects of zinc supplementation on wound healing and metabolic status in patients with diabetic foot ulcer: A randomized, double‐blind, placebo‐controlled trial

Abstract: This study was performed to determine the effects of zinc supplementation on wound healing and metabolic status in patients with diabetic foot ulcer. The current randomized, double-blind, placebo-controlled trial was conducted among 60 patients (aged 40-85 years old) with grade 3 diabetic foot ulcer. Participants were randomly divided into two groups (30 participants in each group) to take either 220 mg zinc sulfate supplements containing 50 mg elemental zinc or placebo daily for 12 weeks. After the 12-week in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 42 publications
(50 reference statements)
0
46
0
6
Order By: Relevance
“…96,97 There has been growing interest in various vitamins and supplements and their impact on wound healing. In 2017, several RCTs evaluated the use of magnesium, omega-3 fatty acids, zinc sulfate, and vitamin D. [98][99][100][101] All of the aforementioned studies showed significant benefits in reduction in wound size when compared with placebo. More studies will need to be performed to validate these findings.…”
Section: Systemic Therapiesmentioning
confidence: 99%
“…96,97 There has been growing interest in various vitamins and supplements and their impact on wound healing. In 2017, several RCTs evaluated the use of magnesium, omega-3 fatty acids, zinc sulfate, and vitamin D. [98][99][100][101] All of the aforementioned studies showed significant benefits in reduction in wound size when compared with placebo. More studies will need to be performed to validate these findings.…”
Section: Systemic Therapiesmentioning
confidence: 99%
“…It is recognized that in individuals with DFUs, infection, antimicrobial agent use, and reduced mobility coupled with possible suboptimal glycaemic control may drive a catabolic state leading to protein energy malnutrition as well as inherent inability to optimize macro and micronutrient usage. 109 We found one study on zinc supplementation, 110 one study on magnesium replacement, 111 one on omega-3 supplementation 112 another on the effect of vitamin D replacement on diabetic foot ulceration, 113 and one on the use of probiotics. 114 All observed an apparent benefit from supplementation, on ulcer length, width, and depth as secondary outcome measures.…”
Section: Rationalementioning
confidence: 99%
“…This was further confirmed by subsequent systemic review, showed that zinc supplementation in T2D patients has improved glycemic control, since the %HbA1c significantly reduced in these individuals [16]. In addition, a recent randomized, doubleblind, placebo-controlled trial confirmed that zinc supplementation for 12 weeks among diabetic foot ulcer patients had beneficial effects on parameters of ulcer size and metabolic profiles [17].…”
Section: Introductionmentioning
confidence: 51%